Studying The Specific Features of Marketing Surveillance in Forming Business Models in Medical Organizations - Jaloliddin O‘g‘li, Abdumalikov Shoxjahon (American Journal of Economics and Business Management, 2025)
This article highlights the role and importance of marketing research in the process of forming modern business models in the activities of medical organizations. Through marketing research, the health status of the population, its needs, and the level of demand for services are determined, and on this basis, an effective set of services is developed. The specific features of marketing in the medical field are determined by the need to adhere to ethical standards, gain the trust of patients, and adapt services to social strata. The article also analyzes practical methods, innovative approaches, and tools such as SWOT analysis used in creating a business model. The results of the research serve to improve strategic planning and quality of service in medical institutions.